Perceptions of Importance and Reported Frequency of Instruction of Self-Determination by Teaching Assistants in New South Wales Schools. Issue 1 (30th July 2022) - Carter, Mark; Webster, Amanda; Stephenson, Jennifer
Abstract: Self-determination skills, including competencies such as decision-making, are regarded by parents and teachers as important for students with special needs. Although not necessarily regarded as appropriate, teaching assistants often take substantial responsibility for delivering educational programs to students and little is known about their perspectives on self-determination. Perspectives of teaching assistants may impact on their support of programs to enhance self-determination that are developed by teachers. Teaching assistants in New South Wales mainstream schools ( N = 320) were surveyed regarding their views on the importance and frequency of instruction of seven competencies related to self-determination of students with special needs. Consistent with previous research, assistants rated all the competencies highly in terms of importance, but frequency of implementation was more variable. Moderate correlations were found between ratings of importance and frequency of implementation, suggesting that greater instructional time was devoted to competencies viewed as more important. Limited differences were found between assistants working at primary and secondary levels. Although features of the interactions of teaching assistants that can inhibit self-determination have been often identified in previous research, it is argued that, paradoxically, assistants may be well positioned to facilitate the development of self-determination with appropriate training and supervision. Directions for future research are identified.